A thisis [sic] on Asiatic cholera - Lammersmann, V. F.(Valentine F.) (Creatorcre)
Listed as Valentine Lammersman in Class of 1865 graduates. Cf. F.C. Waite's Alumni catalogue of the School of Medicine of Western Reserve University. Text in German. English translation: "Asiatic Cholera [PAGE 1] It is common knowledge that the epidemic spread of cholera originated in the East Indies. It seems that in East India the name cholera has been always understood to be two forms of illness, both with heavy bilious diarrhea and that this form corresponds to the more severe form of our Asiatic cholera and the corruption of the French which in [Jan] had used the words Mordixim Mort de Chien [Death of Dog] to name it. Both forms seem to have developed sporadically while at times more frequently – approximately as the cholera [Nostras] with us the latter form seems to have formed in the previous century and later made some larger epidemic expansion, but the disease was during the fall seasons as always limited to the lowest social classes, and the epidemic stopped [babt] achieved little notice. It was only in 1817, after an isolated episode [PAGE 2] in the first half of 1816 that the illness became epidemic in India in larger epidemic propagation and began to take on a wandering character. Already in May of 1817 we find two different epidemics about 40 miles apart geographically. Locations around [Burrumputer] and on the Ganges delta in July was it already a very widespread illness in Fatma far up on the Ganges in August it reigned around the northern corner of Bay of Bengal, Calcutta, Fessore, etc. At the end of September it had generally extended itself over a stretch around 10 degrees. It then spread itself from here to all directions in India so that, although initially, however, some dashes were angry, but at the close of 1818, the disease had crossed the whole East Indian peninsula and was devastated. It is of great interest in this first time of Cholera expansion that tells us some very useful points to emphasize. [PAGE 3] The true starting point of both disease causes is unknown, although there were heavy rains at an atypical season, followed by large floods and less travelling which preceded 1816, but there is absolutely nothing said about Cholera epidemics. The type of disease was completely the same the form of sickness was fully the same, as we later see in Europe. The epidemics began almost everywhere with the utmost nastiness, taking to the intestines and continued indefinitely for a long period of time now and then, but a few remained for only a few days, at most between 14 days and 3 weeks, or yearlong at one site as in Calcutta. Places in high mountain country, namely rocky places, were spared as lower places were moist and densely populated and were infected very severely but sometimes spared during dry periods, apparently healthy areas grew dim through the influence of all the dirtiness. [PAGE 4] And poor bathroom facilities was already noted; the illness rose and fell during all times of the time and during the changing temperatures from 4-40 degrees, during incessant rains and during the largest droughts. The other endemic illnesses such as the Ruhr bilious fever came next as usual. A fullblown beginning was the big influence on both main routes of transport, more strongly infested in the places near the shore than in distant locations. There was also disease chiefly on the country roads and other neighborhoods and it was noted that in small locations, it didn’t break out when another disease already prevailed on the traffic. On a large part of its way towards the southeast, the gift came up against monsoons which brought a strong unbroken stream of fresh sea air with strong rain forward even as the disease appeared in Bombay. [PAGE 5] In Aug 1818 the fact was clear that the disease very frequently broke out in one place when an ill person from elsewhere came to the area. In Bombay itself it was identified, on the other hand, against the usual manner of other illnesses said that as doctors not in higher relationships than any other disease that the most intimate contact with the body of the sick one, the disease doesn’t communicate its influence on the occasion of errors in diet, cold, already honored – but what we report from the East Indian epidemics and what strikes us is most of the subsequent conduct of the illness Europe is very different to the circumstance that in addition to many other horrible, severe epidemics one in ten was very light with a low mortality as low as later, never felt something similar as when Jameson died in the suburbs of Calcutta in 1826, features a warm and treated also was verbal [PAGE 6] The treatment of cholera in India, by the way, already contained all the germs, which are later in the midst of European drugs so richly developed bleeding calomel opium rice wastewater. From 1817 until now, the disease didn’t quite die out in India soon here there came severe epidemic spreading, between 1805 and 1844 cholera was the cause of death among 1/8 of European people and nearly 1/8 under the local troops. The further spread of cholera from India outwards can only be specified in the largest directions. It went next to the east, south, northeast and southeast down to Indian Sumatra Isle over to China, Philippines, Java, [Amboina], etc. only in 1891, and then to the west and north Mascat, Baghdad, Persia Arabia. In 1823 it had reached the shores of the Caspian sea coast [Astracham] of Syria and on the other side the interior seas of Alexandria – very strangely, the stillness that entered here near the threatened European [PAGE 7] lands were spared while still continuing in Asia and continuing in the parts earlier affected in new lands which were searched through. Only in 1824, the illness broke out again on the European borders of Orenburg in 1830, newly in [Astraham] in the first place as it seems to have been brought from Tartary Persia. Again, we find many places very high yet with strikingly low mortality ratios that can hardly be derived from statistical error. More cholera came to Europe from [Astrachan], it pushed next outward and reached into the Volga Valley in 1830. Moscow, roughly 2 hours from [Astrachan], if you pinpoint the beginning of the epidemic in both places credited back to 2 months. Russia was in the course of a year totally overcome and continued to spread west, and the Russian-Polish War of 1831 seems to have contributed. In the year 1831 the first German epidemics occur in the [PAGE 8] north to [Archengel], in the south to Egypt, over to Turkey and one area of Greece, etc. In Germany where the center at that time had a positive vote on the content, as well as poor self-conscious conceit in the medicine before the outbreak of the disease, proud voices could be heard. Here was finally from the [gespence] in Java. Cholera had a beneficially humiliating influence on science and medical practice and simultaneously on epidemiography; compare them to an enemy who shakes violently from the lethargy on the systems and theories which the majority held as irrefutable until today, extended these comforting effects. Cholera, with the large practical problems that it describes, which above all was the gradualness of the endless dying wisdom over Miasma and contagion one end to drop around this preliminary design led fog and shadow and gradual individual examination of the actual [esnersten] [PAGE 10] In 1832 cholera came to London for the first time and over Calais to Paris, and appeared also for the first time in America. In Quebec, the illness appeared at a time when the main current of immigrants was arriving from England, where cholera had prevailed, first in the areas occupied by newcomers and cedants, while the city areas lacking the disembarkation were left alone. Then an outbreak followed in Europe by 1837-38, much-scattered, sometimes more apparent along the borders, coupled epidemics came to the previously disease-free countries of Spain in 1833-34, Sweden in ‘34; to Northern Italy and Munich in 1836, and deposited itself back in Berlin even earlier in 183[?]-37. From the year 1838, Europe was for almost 10 years free of cholera. In the year 1846 Europe experienced a new wave of the epidemic originating from India. It was in this same year unusually widespread, and penetrated this time westward very quickly in the same year over to Persia and the Asiatic [PAGE 11] part of Turkey to Syria and at the same time in the northwest direction towards the high Caucasus. The further spread happened with greater rapidity to the south in Mecca in January 1847, and to the northwest. The epidemic in the Caucasus chain was not only avoided, but rather also directly exceeded to the [heir] street. Moscow was impacted again in September 1847, this time since 1832, after more than 12 years of the epidemic spread from India. In 1848, it was again found extraordinary, that from 1831, the same branch but generally more accelerated, often in big leaps forwards spreading with the whole perhaps in larger intensity of the disease over eastern north and central Europe. Berlin in June, Hamburg by July, and London by September. Norway and Sweden in December, and likewise over the Orient to Turkey and Egypt around the end of the year 1848. The disease also appeared again in the large port cities of the US – New York, New Orleans. [PAGE 12] In the spring of 1849 a new epidemic appeared in Paris where came from Calais in 1832 nearly 10 months this time – 4 months needed in 1853. From Havre to Paris it took hardly 95 days soon upon a large spreading over France, Belgium etc. and in this year through 1850 a larger epidemic was spreading over Germany as before. 1851 was for Germany cholera-free. In 1852 the disease broke out again, it seemed, from Poland, out of the new divide in the eastern parts, spreading itself however not further west to Berlin, under irregular spreading among the various European and non-European countries, paying special attention in 1854 to Italy, Spain, the Orient, and Austria with the epidemic from Vienna in 1855, was excellent in 1854-1855 also for the first time with the exception of past events in [Tessen], in Switzerland with cholera epidemics appearing in Zurich and Basel almost up to the present day. [PAGE 13] The present trend for the year 1856 brought only very small outbreaks to a few German locales (Koenigsberg, etc.). Epidemics occurred in Vienna, while in southern Spain, Portugal and in northern Sweden in parts, larger outbreaks reigned. The course of the epidemic which travelled through Europe beginning in 1848 are so far just like the cholera outbreak in its first major movement. Soon again vanished, the disease now appears far more than earlier in addition to its genesis locations in India and there nested and it seems to be the spread of such points of contagium [erseugte] yet always new epidemics. Nevertheless, one can ask whether one must accept that cholera has become a naturalized, stationary illness in Europe, not quite sure of the answer in [bejahemde] sense, so well it in the year 1838 again disappeared, so well it ceased in Germany in 1850, so well it is very possible or even likely that it stopped again and overall [….] [PAGE 14] Proliferation and Etiology of Asiatic Cholera If one collects the thousands of facts over the spreading of cholera and the manifold representations with which one already searched it under itself in linkage overlooked, then one soon freely encounters above all darknesses, that surely before long enlightenment awaits. One soon finds, however, also a single undoubted fundamental which firmly points to the orientation in which through one terrible mass of detail ready incalculable areas serves, one must then on the behavior one must not so go to work that one through masses so-named negative events that positively firm weakening and darkened the load of every negative event certain facts and wisdoms which are conditional through again other new circumstances but at no time believes it because of this the positive facts [ihres …] [PAGE 15] To assume its essential meaning, that the once-unknown must be securely fixed to the starting point for more careful eye to all the facts, relied on the unknown and wholly dark region, any experiential results are attacked. Cholera was up to now in all epidemics in all zones from the Equator to the area of the polar circle, in the living conditions among the people as possible from the most differentiated types throughout quite the same peculiar disease. Later insignificant deviations in character of single epidemics spent closer to disappear completely from the general way of life from climate and weather and civilizations concluded epidemic and stationary constitutions completely dependent in the same way of the considerable disease processes. The disease was farther in 1830 in Europe unknown and had itself as mentioned in exactly traceable ways out of India there spread these circumstances together [PAGE 16] can on a cause which must be in its consideration very independent from external things. Which cannot in the entire world be created under the varying relationships through collective meetings of external circumstances. Rather, somewhere an active or passive spreading or movement is capable. Shortly on a specific and the spreading [vomeinen] places to the other capable cause that one with hindsight on the cited circumstances and here also rather on the eminent prevailing influence from intoxication then the illness can show to be made unthinkable as cholera poison. This of its circumstances of unknown through its processes undoubtedly manifesting agents this poison is that wandering [rind] spreading the cholera as all other diseases must have poisoned it long again undertook it if it not always new reproduced could as always the cholera occurs … [PAGE 17] We could not have another life, must accept this specific toxic cause may be present, but it shows much of the effect of the poison through certain external relationships often favored and which is required to behave so as to cause cholera [hulfsursachen]. These [hulfsmomente] are apparently on the reproduction of the spatial and temporal spreading of the poison in the intensity of its effects and thus appear to disappear and remain united-staying or the epidemic the lightness and severity of cholera the greatest influence. Where they are missing as the cholera poison seems hardly to adhere and only to reproduce little widespread dissemination and murderous reign of the disease seems to always most locations of mighty [hulfsmommenten] to be dependent. They exist partly in external chemical and physical conditions and on soil conditions, temperature, and atmospheric location. [PAGE 18] Exposure to substances [putuder] dialectic injuries [dergl.] partly given in the dispositions of the population and of the individual. You have these two series of causes, that the poison and the [hulfmommente] of its processes in small and large weal apart around the [actiobuge] of cholera to understand there is where apparently the poison wholly alone without all [comcurence] of another circumstance the disease cause there is other where single [hulfsmommente] so [eclatant] emerge that one is inclined it could over it the specific cause wholly about even without the latter but not young enough to call out the disease. Whether it also on the other hand which against the cholera poison works antagonistically which the same positive destruction or its processes directly digress, we do not know the circumstances which that stops the epidemic things and which editing that in many places where the cholera poison just to get some [sertere] not spreading [stat] fine… [PAGE 19] To accurately assess the spread of cholera through human traffic and to prove, one can only go to where this traffic is observable. Nor can it be at the height of epidemics in larger cities, as with one glance from the bird’s eye view over the spreading of the disease throughout half of or the whole of the world. This proliferation is evident by a few isolated cases, by the movement of troops. Cholera actually spreads itself not in a distinct course to the sky regions [Himmelsgegende]. Earlier it was refuted that advancements of the disease often spread from the east to the west as a set of its spread [d] in the first path across the border of India. Currently it is common knowledge that the spread occurred totally independently of the sky region [Himmelsgegend] soon from south to north out of Italy to Vienna. Cholera spreads itself in large and in small leaps to several places. Never has cholera swept over all countries, but rather in smaller swaths. [PAGE 20] Handling of cholera diarrhea Although one must assume that they are present at the time of the cholera epidemics, many diarrheas occur that are not specifically different from the usual causes alone, that they cannot be distinguished from the specific differences, it is advised that great care observation is taken in all cases of diarrhea n as when there are specific causes. After all, one must therefore identify the most initiating cause if those considered therapeutic , give an emetic if indigestion is evident, or maybe lots of lukewarm water and perhaps traveling [tho] palate. Throwing up in all cases however [erive] be expedient for a stay in bed. Fasting or enjoying only the simplest of nutrients, slime soup, drink from barley water, rubber water, water with some red wine, with a warm covering over the pained abdomen, warm [cattapla], warm baths to transport the warm air [PAGE 21] Transpiration through a warm light, aromatic infusion from melissa menthol, a few of the various medications are next recommended as a time to be stuffed or failing to be the medium of all opium and its various consenting preparations, the mucus of the tannen-containing medium argentums. [Nitrieum] internally and in the [glystriren] the [specacuanha] in infusion in the name of theory only [Vomica] from the stool emptied by a poison the evacuation of the salt medium. [Babarbahr] [calomel] until [Obum] [Crontonis] of all things after many other [Aetheria Oleosa] as [valeriane] [Aleum] menthol mineral sours quinine. This diarrhea [zukommt] and that [dat] is excellent and effective in rest and diet. The experience teaches us that the drugs mentioned in the opium for the great majority of cases is adequate and can be used as [Opi Furum] to ¼ gr to ½ p of the tincture of with [Valeriana] and a bit of [Aleum Menthol]. [PAGE 22] [Fuler Doveri] given especially with obstinate diarrhea applied to the tongue in [elystir ]after the outbreak of opium use stronger and let there remain on strict rest and diet slime, weak aromatic infusions in weaker individuals are to be applied and given strong red wine. Should the diarrhea increase in spite of this, so [rumen] a few especially the [Argentum Nitrieum] internally to gr 1/3 3-4 times daily. Or [Glystiren] is another, [Calomel] to roughly 1 gr every 1-2 hours with one or a little [opi]. Always the general treatment of heating with warm drink liquids for the transportation of transpiration, etc. Are the other [prodomen] or phenomena of the constitution [cholerica] to be treat the mere status [gastricis] with a more or less strict diet. [Brause Fuhr] melissa or chamomile [ther] warning hold the abdomen bei [Nevusen] phenomena [….][Valeria] and opium […] all mediums […] [PAGE 23] Treatment of a Cholera Attack As with diarrhea, so is there for a cholera attack a simple decision, useful and necessary to be used for mass control under all circumstances and probably the most important effective of therapies and a large number of different specific [Tweeduren] and drugs whose efficacy is very doubtful. One of which is primarily covered with warmth [hautuberflor] with wool covers, warm bottles of lemon balm drink, infusions of [flor til] melissa water with a small amount of [braus] powder with heavy wine, thin [saleptdeevet] here given with small pieces of ice if it is absolute fasting here, and a cup of black coffee first after complete termination of the attack. With strong cramps are [frottirungen] the affected muscle parts from use, large synapses could perhaps be expected to contribute to something of warming the skin a bit and with that is also perhaps care maintenance and pure air… [PAGE 24] The simple treatment given during the entire duration of the attack that they make he average much more varied than those applied [Tweeduren] and medicines and show the experience. Whether a somewhat stronger episode in beginning of the attack is really in a position to quickly undo the higherest grade is doubtful, and in any case this application of this medium may cause considerable damage. However, it must be investigated also in cholera cases as usual after the method and empiricism of the prior circumstances surrounded by the weight of the individual elements of the disease and single heavy and more dangerous symptoms and after the individuality of the procedures modified to some extent after, and it can be this individual which the success drove up the use of medicinal instruments. Among the individual proceedings of the attack was soon those…. [PAGE 25] Views to some extent are theoretical views after seemingly empirical occurances to the [hauptanffspunkt] chosen for the therapy in which one is to be accountably investigated what in this regard to reach and from standpoint of our present knowledge the cholera processes appear rational, one has the opportunity the most important of the cholera strongly discouraged medicine and methods minimal contact [kurs] to rest above all only here because to remember that in severe cases namely however in states of asphyxiation only to resort to extraordinary be little or not at all from medicine for the intestines seems that everything that in the stomach and small instestine requires through large portions of fluid drinks and [transsudat] here extraordinarily thinned and some also as soon as one thinks that chemicals in the cooking salt content of the fluids must be replaced and that in any case the greatest portions of the medicine will always be lost through vomiting." Binder's title: Cleveland medical thesis, 1864-1866, v. 28. Holograph. Thesis--Cleveland Medical College, 1865. Cleveland medical theses